Developing rules of thumb for the financial conditions of city livability: a study of municipal governments in Indonesia - Irwan Taufiq Ritonga; Vogy Gautama Buanaputra (Cogent Business & Management, 2022)
This study aims to develop rules of thumb for the financial conditions of city livability. These rules will provide a practical guide for local government leaders managing local government finances on how to realize a livable city. This study identifies three indicators for the financial conditions that characterize a city's livability, namely its operating capacity, financial flexibility, and commitment to maintain services. The standards for each of these three indicators is 1.20 times for the operating capacity ratio, 0.18 times for the financial flexibility ratio, and 0.25 times for the commitment to maintain services ratio.
Keywords: 650; city livability; financial conditions; Indonesia; municipal government; rules of thumb